The History of the Fujiwara House : A Study and Annotated Translation of the Toshi Kaden - Bauer, Mikaël (Book collections on Project MUSE., 2020)
The first annotated translation of the 8th-century clan history Tōshi Kaden or the History of the Fujiwara House. Hitherto, scholars have focused on the 8th-century imperial histories Nihon Shoki and Kojiki, but other sources such as the History of the Fujiwara House provide a narrative that complements or deviates from the official histories.